2018
DOI: 10.1007/s00467-018-4063-7
|View full text |Cite
|
Sign up to set email alerts
|

Periodically repeated rituximab administrations in children with refractory nephrotic syndrome: 2-year multicenter observational study

Abstract: Our protocol was useful and safe for refractory NS. However, RTX administration four times might have been excessive in patients who had no relapse by 1 year after the initial RTX administration. Further investigation of the most appropriate method of RTX administration is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 34 publications
2
24
2
1
Order By: Relevance
“…Complete or partial remission was observed in 40% of the present study's patients, respectively. Some of the SSNS and SRNS patients in the present study received periodic RTX dose, as reported earlier (24). Based on the present findings, we think that such dosing regimens might have a positive effect on remission.…”
Section: Discussionsupporting
confidence: 54%
“…Complete or partial remission was observed in 40% of the present study's patients, respectively. Some of the SSNS and SRNS patients in the present study received periodic RTX dose, as reported earlier (24). Based on the present findings, we think that such dosing regimens might have a positive effect on remission.…”
Section: Discussionsupporting
confidence: 54%
“…A prospective study, aimed at monitoring changes in IgG levels in pediatric steroid-dependent INS treated with repeated rituximab infusions to maintain B-cell depletion for 18 months, reported an increased risk of prolonged hypogammaglobulinemia in patients with pre-existing low IgG levels (10). Reduced IgG levels were also observed after 2 years of a standardized protocol of four single rituximab infusions at 6-months interval in children with difficult-to-treat INS (11). In contrast, a retrospective short-term analysis of anti-CD20-related adverse events in a large cohort of multidrug-dependent INS children treated with rituximab or ofatumumab (a fully human anti-CD20 monoclonal antibody) showed normal total IgG levels and stability of anti-tetanus and anti-hepatitis B virus (HBV) IgG titers, albeit at 12-months (12).…”
Section: Introductionmentioning
confidence: 95%
“…Takahashi reported on the efficacy of a single rituximab infusion given routinely, regardless of proteinuria, every 6 months for 2 years in children with SRNS. Although this helped in controlling the NS, it was associated with significant side effects, making further studies important before this approach could be widely recommended (93).…”
Section: Factors That May Affect the Clinical Response Of Rituximab Imentioning
confidence: 99%
“…B cell recovery has been used in some protocols to indicate the need for another dose of rituximab to maintain B cell depletion and NS remission (36, 93, 111). Although this approach has been reported to be beneficial in these studies, larger studies are still needed to validate this practice, since it is also known that some individuals can experience NS relapses despite having B cell depletion (36, 49, 112), and repeat dosing of rituximab based on B cell reconstitution rather than NS relapse may expose children to unnecessary rituximab treatment and increase the risk of drug-induced complications.…”
Section: Biomarkers Of Response To Rituximabmentioning
confidence: 99%